PTU-025 Obesity is associated with severity and outcome of alcoholic hepatitis. (June 2019) - Moodley, Prebashan; Dhanda, Ashwin
Abstract : Introduction: Both sarcopenia and adiposity can influence the prognosis of patients with chronic liver disease. However, little is known of their interaction in patients with alcoholic hepatitis (AH). With the changing demographics of gender, age and body shape of AH patients, it is important to understand how obesity and sarcopenia affect AH severity and outcome. We aimed to determine whether quantity of skeletal muscle and adipose tissue influenced the outcome and severity of AH patients. Methods: We studied a prospective single centre cohort of patients with severe AH, defined as recent onset jaundice (bilirubin>80 µmol/L) in heavy alcohol drinkers (>80g ethanol/day in males; >60g in females), AST:ALT>2 and discriminant function (DF)>32. Patients received standard medical care including 28 days of corticosteroids in the absence of active infection. Clinical and laboratory parameters were obtained at baseline and patient survival recorded at 6 months. CT scans from patients taken within 3 months of their index presentation were evaluated for adipose tissue and skeletal muscle area. An image at the level of L3/4 vertebrae was analysed using ImageJ software according to published methodology (Gomez-Perez, JPEN 2016) and total abdominal, intra-peritoneal and skeletal muscle areas were measured. Results: Of a total 28 patients, 21 (mean age 49, DF 74, MELD 19; 11 females) had an eligible CT scan and were included in the final analysis. There were 5 deaths within 6 months (2 females). Total abdominal area was higher in non-survivors vs survivors at 6 months (1010 v 715 cm 2 ; p=0.003) and correlated with severity of AH measured by MELD (r=0.50; p=0.04). Waist circumference and adipose tissue area were higher in non-survivors than survivors at 6 months (126 v 105 cm; p=0.02 and 576 v 406 cm 2 ; p=0.05, respectively). Skeletal muscle area was no different between non-survivors and survivors (141 v 121 cm 2 ; p=0.37). Multivariate analysis with total abdominal area, age, bilirubin, albumin, urea and MELD as co-variates showed that total abdominal area is an independent predictor of 6-month outcome in this dataset (p=0.003). Conclusions: These data demonstrate that adiposity but not sarcopenia is associated with severity and predicts outcome of AH. Obesity should be recognised as a risk factor in patients with AH. Greater understanding of the interaction between alcohol and adipose tissue in AH may reveal new targets for treatment.